In Vitro Evaluation of The Antifungal Activity of Breadfruit (Artocarpus altilis) Leaves Extract Againts Puccinia arachidis, Causative Agent of Groundnut Rust - Jumar, Jumar; Perdana, Arga Kusuma; Saputra, Riza Adrianoor; Sari, Noorkomala (Hasanuddin University, 2024)
Breadfruit (Artocarpus altilis) leaves contain several antimicrobial properties such as saponins, hydrocyanic acid, polyphenols, acetylcholine, potassium, tannin, phenol, riboflavin, and flavonoids. Phenol is a compound found in plants that causes pesticide effects. Previous studies have demonstrated that breadfruit leaf extract contains phenol compounds with antimicrobial activity and can be used as a fungicide. The purpose of this study was to determine the effect of breadfruit leaf extract on the growth inhibitory power and percentage inhibition of Puccinia arachidis spore germination as well as the best concentration of breadfruit leaf extract in inhibited the growth of Puccinia arachidis, an agent causing groundnut rust disease in peanut plants in food poisoning method. This study used a single factor CRD consisting of 5 treatment levels, namely k0(-) = negative control, k0(+) = positive control, k1 = 10 % extract concentration, k2 = extract concentration of 20 %, and k3 = extract concentration of 30 %. The results of this study indicate that the breadfruit leaf extract significantly affected Puccinia arachidis growth with the presence of percentage inhibition of Puccinia arachidis spore germination. The highest concentration of breadfruit leaf extract as a rust disease biofungicide (Puccinia arachidis) in peanut plants in vitro at a concentration of 30 %.